Influence of Grain Size on Phase Transitions in Halide Perovskite Films. Issue 35 (7th August 2019) - Stavrakas, Camille; Zelewski, Szymon J.; Frohna, Kyle; Booker, Edward P.; Galkowski, Krzysztof; Ji, Kangyu; Ruggeri, Edoardo; Mackowski, Sebastian; Kudrawiec, Robert; Plochocka, Paulina; Stranks, Samuel D.
Abstract: Grain size in polycrystalline halide perovskite films is known to have an impact on the optoelectronic properties of the films, but its influence on their soft structural properties and phase transitions is unclear. Here, temperature‐dependent X‐ray diffraction, absorption, and macro‐ and micro‐photoluminescence measurements are used to investigate the tetragonal to orthorhombic phase transition in thin methylammonium lead iodide films with grain sizes ranging from the micrometer scale down to the tens of nanometer scale. It is shown that the phase transition nominally at ≈150 K is increasingly suppressed with decreasing grain size and, in the smallest grains, the first evidence of a phase transition is only seen at temperatures as low as ≈80 K. With decreasing grain size, an increasing magnitude of the hysteresis is also seen in the structural and optoelectronic properties when cooling to, and then upon heating from, 100 K. This work reveals the remarkable sensitivity of the optoelectronic, physical, and phase properties to the local environment of the perovskite structure, which will have large ramifications for phase and defect engineering in operating devices. Abstract : Temperature‐dependent X‐ray diffraction, absorption and photoluminescence measurements on methylammonium lead iodide thin films with grain sizes ranging from the micrometer to the tens of nanometer scale reveal that the low‐temperature phase transition is increasingly suppressed with decreasing grain size. These results unveil the remarkable sensitivity of optoelectronic and structural properties to the local environment in perovskite thin films.